Descriptive Spatial Analysis of the Distribution of Green Open Spaces (RTH) and Fast Food Stalls on the Prevalence of Hypertension Cases in Surabaya City in 2024 - Gifta Azzahra Aulindra Subekti (CV. Inara, 2026)
The massive urbanization transformation in Surabaya City has triggered the commercial expansion of fast food outlets, creating an obesogenic environment, while simultaneously threatening the existence of public Green Open Spaces (GOS) which are essential for cardiovascular health, including hypertension. This study aims to descriptively analyze the spatial correlation between the distribution of GOS and the accessibility of fast food outlets on the prevalence of hypertension cases in Surabaya City in 2024. This study uses a descriptive spatial analysis method at the sub-district analysis unit in Surabaya City. Secondary data on GOS area, Health Profile, and fast food outlet coordinates from OpenStreetMap were analyzed using overlay techniques and chloropath mapping through QGIS 3.34.3 software. The results of the analysis show significant spatial disparities. Sukolilo and Rungkut Districts have high exposure to fast food outlets, but their hypertension cases are controlled because they are balanced by the largest GOS area. In contrast, high hypertension hotspot areas (12–26%) were identified in Semampir, Pabean Cantian, and Karang Pilang Districts, which have very critical GOS availability (0–5,542 m²). There is an imbalance in the distribution of Green Open Space (RTH) and fast food restaurant clusters that indirectly correlates with the disparity in the prevalence of hypertension cases between sub-districts in Surabaya City in 2024.